Purification, Characterization, and Structural Studies of a Sulfatase from Pedobacter yulinensis - Caleb R. Schlachter; Andrea O’Malley; Linda L. Grimes; John J. Tomashek; Maksymilian Chruszcz; L. Andrew Lee (Molecules, 2021)
Sulfatases are ubiquitous enzymes that hydrolyze sulfate from sulfated organic substrates such as carbohydrates, steroids, and flavones. These enzymes can be exploited in the field of biotechnology to analyze sulfated metabolites in humans, such as steroids and drugs of abuse. Because genomic data far outstrip biochemical characterization, the analysis of sulfatases from published sequences can lead to the discovery of new and unique activities advantageous for biotechnological applications. We expressed and characterized a putative sulfatase (PyuS) from the bacterium Pedobacter yulinensis. PyuS contains the (C/S)XPXR sulfatase motif, where the Cys or Ser is post-translationally converted into a formylglycine residue (FGly). His-tagged PyuS was co-expressed in Escherichia coli with a formylglycine-generating enzyme (FGE) from Mycobacterium tuberculosis and purified. We obtained several crystal structures of PyuS, and the FGly modification was detected at the active site. The enzyme has sulfatase activity on aromatic sulfated substrates as well as phosphatase activity on some aromatic phosphates; however, PyuS did not have detectable activity on 17α-estradiol sulfate, cortisol 21-sulfate, or boldenone sulfate.